Awareness Of Tax In Nepal - Sanju Kumar Singh; Jitendra Prasad Upadhyay; Paras Mani Acharya (ABM: International Journal of Administration, Business and Management, 2024)
This study analyzed the awareness of tax in Nepal. Additionally, the study seeks to address the Nepalese tax payers awareness specially on VAT and income tax. Out of total population data were collected by 630 participants and analyzed using thematic analysis. All the data were collected using a well-structured questionnaire. For analysis and interpretation SPSS has been used. The findings of the result clearly explain that Nepalese taxpayers do not have sufficient technical knowledge and perceive the VAT and income tax system. Similarly, it was found that the majority of consumers pay tax but are less aware of VAT. Consumers avoid paying tax in Nepal as VAT tends to be high.